2017
DOI: 10.18203/2320-1770.ijrcog20170025
|View full text |Cite
|
Sign up to set email alerts
|

Study to evaluate association of umbilical coiling index and perinatal outcome

Abstract: Background: To correlate the perinatal outcome by noting the umbilical coiling index.Methods: The umbilical cords of the babies born to 500 women, who delivered either vaginally or by lower segment caesarean section, were examined and umbilical coiling index was calculated.Results: There was significant correlation (p value 0.003) between. Hypercoiling (UCI >90th percentile) is associated with IUGR. Hypocoiling (UCI <10th percentile) is associated with: - Meconium staining liquor, high LSCS rates, low Ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 4 publications
2
5
0
Order By: Relevance
“…Monique et al [14] found that hypocoiling was associated with small for gestational age infants. Chholak D et al [2] , Georgiou et al [13] , Shayesta Rahi et al [16] , and Ezimokhai M et al [17] obtained similar results in their studies Meconium staining of the amniotic fluid was found to be associated with Hypocoiled Umbilical Cords (p value 0.003) in our study. Similar findings were noted in studies done by Strong et al [10] and Ezimokhai et al [17] .…”
Section: Discussionsupporting
confidence: 85%
“…Monique et al [14] found that hypocoiling was associated with small for gestational age infants. Chholak D et al [2] , Georgiou et al [13] , Shayesta Rahi et al [16] , and Ezimokhai M et al [17] obtained similar results in their studies Meconium staining of the amniotic fluid was found to be associated with Hypocoiled Umbilical Cords (p value 0.003) in our study. Similar findings were noted in studies done by Strong et al [10] and Ezimokhai et al [17] .…”
Section: Discussionsupporting
confidence: 85%
“…Ezimokhai M et al and Chholak D et al obtained similar results in their studies. 4,11 In present study, 60% of babies in hypercoiled group had birth weight <2.5kgs and none from hypocoiled group had birth weight <2.5kgs, which was statistically significant (p value <0.001). Similar association between hypercoiling and low birth weight was seen in studies conducted by Rana J et al and Raio L et al 6,12 In present study percentage of NICU admission was more (40%) in both hypocoiled and hypercoiled groups as compared to normocoiled group.…”
Section: Discussionsupporting
confidence: 45%
“…Additionally, Chholak et al found that hypercoiled and IUGR had a significant relationship with hypochondrium, meconium excrement, apheresis below seven in the first and fifth minutes, and the need for admission to NICU (24).…”
Section: Discussionmentioning
confidence: 99%